The association between shift work and body mass index among female nurses - Samara, Diana; Merijanti, Lie T; Tandean, Reza; Harrianto, Ridwan (Universa Medicina, 2008)
Possibly due to a disturbance of biological rhythms, shift work is associated with several health problems, particularly an increased risk of coronary heart disease (CHD). Obesity is a well known independent cardiovascular risk factor and has been shown to be more prevalent among shift workers. The objective of this study was to examine the association between shift work and body mass index in nurses working in one hospital in Central Jakarta. A cross-sectional study was conducted among 152 female nurses, ranging from 22 to 55 years of age, with determination of body mass index (BMI), and systolic and diastolic blood pressure (SBP and DBP). The results show a mean age of 30.9 ± 7.2 years and mean job experience of 8.9 ± 7.6 years. There was no significant difference in the prevalence of gastrointestinal disorders between shift and day workers. Mean BMI (23.1 ± 3.6) and mean job experience (6.9 ± 5.9 years) in shift nurses were significantly different from those in day workers (BMI = 24.8 ± 3.8; job experience 15.4 ± 8.4 years). In shift working nurses the BMI increased significantly in proportion to job experience (p=0.014). In conclusion, the present study has proven that job experience significantly increased BMI in shift working nurses.